User Readiness and Digital Bureaucratic Transformation in Local Government: Evidence from SRIKANDI Adoption in Surakarta City - Ni’mah, Fahmi Ulin; Kartikasari, Hanum; Khadija, Mutiara Auliya; Jayanti, Ida Setya Dwi (Journal of Local Government Issues, 2026)
This study examines civil servants’ readiness to adopt the SRIKANDI digital archival system within the Surakarta City government as part of broader efforts toward digital bureaucratic transformation in local government administration. The research applies the Technology Readiness Index (TRI) framework to analyze how psychological factors influence users’ intention to utilize the system. TRI conceptualizes technological readiness through four dimensions: optimism, innovativeness, discomfort, and insecurity. A quantitative approach was employed using purposive sampling, involving 105 civil servants responsible for archival management across local government organizations, technical units, and district offices in Surakarta City. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that optimism and innovativeness significantly increase civil servants’ intention to use the SRIKANDI system, while discomfort and insecurity negatively influence adoption. Among these factors, insecurity demonstrates the strongest influence, suggesting that trust and perceived technological risks play a critical role in shaping digital system adoption within bureaucratic environments. These findings highlight that the successful implementation of digital archival systems in local government institutions is not solely determined by technological infrastructure but also by the psychological readiness of civil servants and the organizational context in which they operate. From a policy perspective, local governments need to complement technological innovation with capacity-building programs, user support mechanisms, and trust-building strategies to ensure the effective adoption of digital governance systems. This study contributes to the literature on e-government and digital bureaucracy by providing empirical evidence on how technological readiness shapes digital transformation within local government organizations.